ANALISIS EFEKTIVITAS PROSES PENCAIRAN DANA PADA KANTOR PELAYANAN PAJAK PRATAMA BEKASI UTARA - Natrion (Jurnal Liabilitas, 2022)
The purpose of this study is to see whether the variables of supervision, Human Resources (HR), Standard Operating Procedures (SOP) and Information Systems affect the effectiveness of the disbursement process at Kantor Pelayanan Pajak Pratama Bekasi Utara. The research methodology used in this study uses clauses to identify the extent and nature of cause-and-effect relationships. The population and sample are Pejabat Pembuat Komitmen (PPK) from Work Units and Partners who are registered in the Bekasi KPPN environment. The type of data used in this study is primary data obtained directly from the original source (without going through an intermediary) by using an online questionnaire distribution technique. The data analysis method used to test this research is in the form of descriptive statistical analysis, validity test, reliability test, classical assumption test, multiple linear regression test and hypothesis testing Based on the results of this study, the Supervision Variables, Human Resources (HR), Standard Operating Procedures (SOP), have no effect on the effectiveness of the disbursement process, but Information System variables affect the effectiveness of the disbursement process at the Kantor Pelayanan Pajak Pratama Bekasi Utara.